PEMBENTUKAN JIWA WIRAUSAHA MAHASISWA UNIVERSITAS MUHAMMADIYAH SURAKARTA MELALUI PROGRAM WIRAUSAHA MERDEKA - Aimar Fadhly Muhammad; Daryono Soebagyo (Universitas Muhammadiyah Surakarta, 2024)
The increasing number of unemployed in Indonesia has encouraged the government to innovate with the independent entrepreneurship program. This activity was carried out at Leather Lovers UMKM with two objectives: (a) increasing knowledge and entrepreneurial skills in the tofu processing business; and (b) provide entrepreneurial mental strength to students who take part in the entrepreneurial internship program. Direct action is used in internship programs for business creation, business planning models, production, and marketing. This is done through direct and interactive learning methods. Five students took part in activities for six months which included business planning, production, cost of goods manufactured, cost of goods sold, and packaging, and online and offline marketing. The MSME internship program increases entrepreneurial mentality and entrepreneurial spirit through training and business mentoring stages. The results after six months of activities show that the students' entrepreneurial mentality has increased and their desire to try has increased.